TAMANHOS MÍNIMOS AMOSTRAIS PARA DETECTAR A PRESENÇA DE NEMATÓIDES EM VIVEIROS DE PRODUÇÃO DE MUDAS DE CAFÉ - MUNIZ, Joel Augusto; LIMA, Renato Ribeiro de; FERREIRA, Daniel Furtado; QUEIROZ, Leidiane Aparecida Ferreira; PEREIRA, José Maurício (Brazilian Journal of Biometrics, 2019)
The Normative Instruction no35/2012, of the Minist´erio da Agricultura, Pecu´aria e Abastecimento, from Brazil, provides the rules for sampling in nurseries of coffee seedlings production, for verification of defective roots and detection of Meloidogyne spp. Sampling is performed by dividing the nursery into plots of a maximum of 200,000 seedlings of the same cultivar and subdividing each plot into four subplots. The aim of this work was to evaluate the need to carry out the sampling considering subplots as recommended in the Normative Instruction, seeking to reduce the production cost of the small producers, without prejudice to sanitary measures. For this purpose statistical estimates were calculated based on a probability study, considering the Poisson distribution for the random variable X, which expresses the amount of nematodes per coffee seedling in the nursery phase, based on the actual data of five years of all coffee seedlings nurseries of Minas Gerais State-Brazil. It was concluded that subdivision into subplots may be dispensed when the total number of seedlings of the same cultivar does not exceed 50000, without loss of accuracy in the detection of the pathogen.